2003
DOI: 10.1517/14656566.4.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of heparin-induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is a life-and-limb threatening condition that is associated with the development of antibodies that activate platelets and the coagulation system in the presence of unfractionated heparin or low molecular weight heparin. The binding of antibody to heparin-PF-4 complexes can activate platelets, leading to an acute, often catastrophic, thrombotic diathesis. The most common laboratory finding is the development of thrombocytopenia 5 or more days after beginning heparin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…8 CXCL4 has also been proposed to play critical role in other human diseases including heparin-induced thrombocytopenia (HIT) and progression of multiple myeloma. 29,30 During evolution, recent gene duplication gave rise to a second CXCL4 form, named PF4alt/PF4V1 or CXCL4L1. 31 CXCL4L1 is only found in some primates.…”
Section: Org Frommentioning
confidence: 99%
“…8 CXCL4 has also been proposed to play critical role in other human diseases including heparin-induced thrombocytopenia (HIT) and progression of multiple myeloma. 29,30 During evolution, recent gene duplication gave rise to a second CXCL4 form, named PF4alt/PF4V1 or CXCL4L1. 31 CXCL4L1 is only found in some primates.…”
Section: Org Frommentioning
confidence: 99%
“…These clinical study data showed significant risk reductions in clinical outcomes (all-cause death, all-cause amputation, and new thrombosis within 37 days of baseline) relative to historical controls (Table 7) (66). Rates of death in argatroban-treated patients ranged from 16.9% to 23.1% compared with 20.9% to 28.3% in the historical control groups.…”
Section: Treatment Of Hitmentioning
confidence: 81%
“…The ELISA can be performed relatively quickly and has high sensitivity (90 -98%) and high negative predictive value (95%); however, it has a low specificity with a moderately high false-positive rate in patients who have received heparin between 5 days to a few weeks earlier. The presence of HIT antibodies does not necessarily predict the development of clinical HIT (66). A positive ELISA test for HIT antibodies occurs in approximately 3-20% of patients treated with heparin (37), and this percentage is even higher (40 -60%) after open heart surgery, yet relatively few of these patients develop HIT (67)(68)(69).…”
Section: Diagnosis Based On Clinical Features and Onset Relative To Rmentioning
confidence: 99%
“…In the emergent intervention of acute coronary syndromes and myocardial infarction, heparin is often given. It is important to distinguish the cause of thrombocytopenia because heparin itself may also induce this effect 16 . Heparin may elicit a direct or enhancing effect of other platelet‐aggregating substances, resulting in mild platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Nadir platelet counts usually fall to <100×10 9 /L or to 50% below baseline. Heparin‐PF4 antibody—as well as serotonin‐releasing assay—may differentiate between the types of heparin‐induced thrombocytopenia and definitively rule out heparin as the suspect in the cause of profound thrombocytopenia 16 …”
Section: Discussionmentioning
confidence: 99%